Distinct binding determinants for 9-cis retinoic acid are located within AF-2 of retinoic acid receptor alpha. - Tate, B F (1994)
Retinoids exert their physiological action by interacting with two families of nuclear receptors, the retinoic acid receptors (RARs) and the retinoid X receptors (RXRs), which regulate gene expression by forming transcriptionally active heterodimeric RAR/RXR or homodimeric RXR/RXR complexes on DNA. Retinoid receptor activity resides in several regions, including the DNA and ligand binding domains, a dimerization interface, and both a ligand-independent (AF-1) and a ligand-dependent (AF-2) transactivation function. While 9-cis retinoic acid (RA) alone is the cognate ligand for the RXRs, both 9-cis RA and all-trans RA (t-RA) compete for binding with high affinity to the RARs. This latter observation suggested to us that the two isomers may interact with a common binding site. Here we report that RAR alpha has two distinct but overlapping binding sites for 9-cis RA and t-RA. Truncation of a human RAR alpha to 419 amino acids yields a receptor that binds both t-RA and 9-cis RA with high affinity, but truncation to amino acid 404 yields a mutant receptor that binds only t-RA with high affinity. Remarkably, this region also defines a C-terminal boundary for AF-2, as addition of amino acids 405 to 419 restores receptor-mediated gene activity to a truncated human RAR alpha lacking this region. It is interesting to speculate that binding of retinoid stereoisomers to unique sites within an RAR may function with AF-2 to cause differential activation of retinoid-responsive gene pathways.